Landscape patterns shape wetland pond ecosystem function from glacial headwaters to ocean - Vizza, Carmella; Zwart, Jacob A.; Jones, Stuart E.; Tiegs, Scott D.; Lamberti, Gary A. (Limnology and oceanography, 2017)
Examining patterns and processes along the aquatic continuum from headwaters to ocean can benefit from a landscape ecology approach, where hydrologic and ecological processes depend on landscape position. We conducted a study of freshwater wetland ponds subject to similar climatic conditions but distributed along a 20-km trajectory from glacial headwaters to ocean in southcentral Alaska, U.S.A. Specifically, we investigated how proximity to glaciers and ocean influenced physical, chemical, and biological characteristics of ponds. Physicochemical patterns along a distance gradient from the ocean supported the hypothesized influence of elevation and potential atmospheric deposition of marine-derived nitrogen, whereas those related to glacial flow path length may reflect inputs from glacial weathering. We expected that the effects of landscape and hydrology on physicochemical patterns would provide a template for shaping ecosystem processes, but ecosystem processes also appeared to contribute to physicochemical patterns across this landscape. Ponds more heavily influenced by glaciers tended to be more heterotrophic exhibiting greater rates of organic-matter decomposition and ecosystem respiration, which were positively correlated with phosphorus and iron concentrations likely due to glacial weathering and remineralization processes. In contrast, ponds near the ocean tended to be more autotrophic exhibiting greater gross primary production and net ecosystem production, processes that may have contributed to greater total nitrogen, nitrogen to phosphorus ratios, and dissolved organic carbon concentrations. Consideration of the relative importance of hydrologic inputs across the landscape is needed because the acceleration of glacial melt and sea-level rise by climate change may alter future broad-scale patterns of ecosystem processes.